2015
DOI: 10.1186/s12934-015-0238-0
|View full text |Cite
|
Sign up to set email alerts
|

High production of ectoine from aspartate and glycerol by use of whole-cell biocatalysis in recombinant Escherichia coli

Abstract: BackgroundRecently, the compatible solute 1, 4, 5, 6-tetrahydro-2-methyl-4-pyrimidinecarboxylic acid (ectoine) has attracted considerable interest due to its great potential as a protecting agent. To overcome the drawbacks of high salinity in the traditional bioprocess of ectoine using halophilic bacteria, various attempts have been made to engineer ectoine biosynthesis in nonhalophilic bacteria. Unfortunately, the yields of ectoine in these producers are still low and hardly meet the demands of large scale pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 35 publications
0
32
2
Order By: Relevance
“…Aspartate is the biosynthetic precursor of ectoine (20,86) (Fig. 1A), and its addition to the growth medium has already been proven beneficial for the recombinant production of ectoines (87). In exploratory experiments, we observed that the addition of 25 mM aspartate to our Ots Ϫ E. coli cell factory harboring plasmid pLC68 substantially enhanced hydroxyectoine production (see Fig.…”
Section: Gene Disruptionmentioning
confidence: 88%
See 1 more Smart Citation
“…Aspartate is the biosynthetic precursor of ectoine (20,86) (Fig. 1A), and its addition to the growth medium has already been proven beneficial for the recombinant production of ectoines (87). In exploratory experiments, we observed that the addition of 25 mM aspartate to our Ots Ϫ E. coli cell factory harboring plasmid pLC68 substantially enhanced hydroxyectoine production (see Fig.…”
Section: Gene Disruptionmentioning
confidence: 88%
“…9B and E). It shares this feature with other synthetic cell factories that rely on microbial chassis strains that do not produce ectoines naturally (61)(62)(63)(64)(65)87). Investigations into the release of hydroxyectoine from a recombinant E. coli strain expressing the ectD gene from P. stutzeri A1501 under the control of the tet promoter (85) demonstrated that this process was not mediated, in the absence of an osmotic downshock, by any of the mechanosensitive channels (MscL, MscS, and MscM) operating in E. coli (100).…”
Section: Discussionmentioning
confidence: 99%
“…The retention time: the spectra signal of LC-MS analysis (pseudo-molecular ion at m/z 143) (Fig1a) and LC-MS/MS analysis (product ions at m/z 143.3, 97.0, 68.2, 55.9, and 44.0) (Fig 1b) were all in agreement with the data of the authentic ectoine. Therefore, the compound in the cells alcoholic extract was identified as ectoine [38]. Seed germination is the most critical stage during the life span of most plants, a lot of plants can survive and tolerate abiotic stresses when safely pass this stage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can be used in whole cell biocatalysis for production of metabolites . It was also used in ectoine production from aspartate‐semialdehyde and high ectoine concentration was achieved . In the current study using the same strategy, the cells were collected by centrifugation and subjected to whole cell biocatalysis.…”
Section: Feasibility Of 23‐bd Production By Whole Cell Biocatalysismentioning
confidence: 99%